2014
DOI: 10.7763/ijiet.2014.v4.361
|View full text |Cite
|
Sign up to set email alerts
|

Producing Lecture Videos from Face-to-Face Teaching

Abstract: Abstract-There is a clear demand for lecture videos in modern education. Nevertheless, the desire to keep face-to-face education remains as well. In such a case, the natural option is to produce videos in face-to-face teaching situations rather than in a studio environment. The challenge this kind of production faces is how to make it to cover an entire degree program cost-efficiently while serving the purpose intended. This article explains the demands set for video production in the context of face-to-face e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Reliability was naturally increased by the experience gained from the technologies and the practices formed around them. According to research, the production at this stage was very reliable: during 2008-2010, the success rate was approximately 99%, and in 2011 it was already about 99.4% [10].…”
Section: Stage 3: Distance Learning Becomes Possiblementioning
confidence: 99%
See 1 more Smart Citation
“…Reliability was naturally increased by the experience gained from the technologies and the practices formed around them. According to research, the production at this stage was very reliable: during 2008-2010, the success rate was approximately 99%, and in 2011 it was already about 99.4% [10].…”
Section: Stage 3: Distance Learning Becomes Possiblementioning
confidence: 99%
“…One could, therefore, assume that the extent to which the technologies are utilized indicates that the model is approved by students. The distribution of participation through face-to-face learning and with the help of lecture videos has been investigated in the previous research [10]. The investigation showed that the utilization of the technologies for participation in education plays a fairly important role.…”
Section: A Blendingmentioning
confidence: 99%
“…For years now, video participation has had a significant role in participating in the degree programme [18]. During the realisation of the education programme, it has been noted that participation in contact teaching has diminished up to the point of near non-existence over the years.…”
Section: Research Environmentmentioning
confidence: 99%